Daniel Boone, trail blazer - Hubbard, Thomas G., 1919-1974; Patrick, John, 1905-1995; Bennett, Bruce, 1906-2007; Chaney, Lon, Jr., 1906-1973; Young, Faron (Republic Pictures, 1956)
Boone and his band of settlers travel from North Carolina to Kentucky. The Shawnee Indians are incited to fight the settlers by French renegades and some British Redcoats. Boone saves the day by convincing the Shawnee Chief that the settlers want nothing but peace.